Determinants of private banks performance in Ethiopia: A partial least square structural equation model analysis (PLS-SEM) - Million Adafre Bushashe (Cogent Business & Management)
This study examines the factors affecting Ethiopia’s private bank performance. The study followed a causational research design employing data from 2010–to 2021. The study unit of analysis is Eleven private banks in Ethiopia. The study also uses PLS-SEM with Gaussian copula (GC) estimation because of its advantage in resolving econometric concerns of endogeneity. According to the study’s findings, industry-specific factors and macroeconomic variables have a negative statistically significant effect on bank performance. On the other hand, bank-specific factors have statistically positively affected both bank performance and the banking industry. Besides, industry-specific positively mediates the relationship between bank-specific factors and bank performance. The macroeconomic variables do not affect bank and industry-specific variables. Since Bank-specific factors enhance profit and industry (market share), continuous supervision and assistance from stakeholders can prevent banks from failing, improve their financial performance, and neutralize the industry’s adverse effect on the bank performance. Also, its mediating role through increasing the private banks’ market share may be due to the leading government-owned bank’s monopoly over the banking industry. The failure of banks could lead to the collapse of the entire economy. The current study fills a vacuum in the body of literature because it considers previously overlooked factors that affect bank performance, i.e., industry-specific variables and their mediating role on the effect of bank-specific factors on bank performance.